Application of Topographical Keratoconus Detection Metrics to Eyes of Individuals with Down Syndrome. Issue 9 (September 2019) - Marsack, Jason D.; Benoit, Julia S.; Kollbaum, Pete S.; Anderson, Heather A.
Abstract : SIGNIFICANCE: The challenges associated with clinical assessment of individuals with Down syndrome contribute to a wide range of estimates on the prevalence of keratoconus in the Down syndrome population. This work focuses on two topographical indices previously identified with keratoconus detection, applying them to a topographical data set meeting strict sampling criteria. PURPOSE: The purpose of this study was to quantify the level of keratoconus-like topographical morphology in a large sample of eyes from individuals with Down syndrome, as identified by two keratoconus detection metrics: inferior-superior dioptric asymmetry (I-S) and KISA%. Severity of the asymmetry was also cast within the context of established Collaborative Longitudinal Evaluation of Keratoconus study disease severity classification criteria. METHODS: Corneal topography data on both eyes of 140 subjects with Down syndrome and 138 control subjects were collected. Both I-S and KISA% were calculated from the topography data of eyes with sufficient sampling. Steep and flat keratometry data are reported for subjects with measurements on both eyes in the context of values recorded by the Collaborative Longitudinal Evaluation of Keratoconus study in frank keratoconus to examine within-eye and between-eye asymmetry and severity. RESULTS: Keratoconus detection thresholds were exceeded in 20.8% of the eyes of subjects with Down syndrome and 2.2% of the eyes of controls using I-S and 11.8% of the eyes of subjects with Down syndrome and 0.0% of the eyes of controls using KISA%. Examination of the level of intraeye difference between flat and steep keratometry data for individuals with Down syndrome detected as having corneal morphology consistent with moderate keratoconus yields an average of 1.81 D of toricity, whereas the Collaborative Longitudinal Evaluation of Keratoconus study reported 3.28 D of toricity. CONCLUSIONS: Morphology consistent with keratoconus as codified in the detection metrics I-S and KISA% is present in a large percentage of the eyes of individuals with Down syndrome. Differences were observed in the distribution of severity of corneal morphology in individuals with Down syndrome and the keratoconus population at large.